La suerte del minero : energía, oro y valor en Marmato, Caldas (2017)
"In this text I explore the ways in which the "traditional" miners in a Colombian town, Marmato, create value in the relationship they establish between their persona as extractive agents and gold as a mysterious agent. I depart from two central ethnographic concepts, luck and energy, to understand how, from the miner's perspective, the gold hidden in the mountain and merged into the rock emerges to whom it corresponds to find it. For the miners in Marmato gold is above all mysterious, since it has the ability to hide itself from those who seek it with ambitious desires, which is considered bad energy, or appear to those who seek it without anxiety, which is considered positive energy. In this way, luck does not emerge as a rational randomness, but as something that is inseparable from the miner as a person." -- Tomado del Formato de Documento de Grado.